2021
DOI: 10.21608/mid.2021.64549.1128
|View full text |Cite
|
Sign up to set email alerts
|

Upshot of virulence markers and effects of temperature and pH on haemolytic bacteria in South-west Nigeria

Abstract: Background: Virulence is the extent of pathogenicity displayed by majority of pathogens and yardstick that efficiently distinguishes pathogenic and non-pathogenic organisms. Effects of pH, temperature and incubation period were studied on capsulepositive bacteria isolated from Onyearugbulem stream, Akure. Methods: Water samples from Onyearugbulem stream in Akure was collected in sterile 500ml sample bottles. Water samples obtained from the stream were subjected to microbiological analysis. Implicated bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…One of the most important natural resources is water which is essential in the life of all living organisms. However, excess runoff of sewage and fertilizers into freshwater bodies provides a favorable environment for the growth and reproduction of pathogenic microorganisms [ 1 ]. It is reported that river water is usually contaminated by diverse groups of pathogenic bacteria [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important natural resources is water which is essential in the life of all living organisms. However, excess runoff of sewage and fertilizers into freshwater bodies provides a favorable environment for the growth and reproduction of pathogenic microorganisms [ 1 ]. It is reported that river water is usually contaminated by diverse groups of pathogenic bacteria [ 2 ].…”
Section: Introductionmentioning
confidence: 99%